A New Hybrid MCDM Model for Insulation Material Evaluation for Healthier Environment - Aksakal, Berrak; Ulutas, Alptekin; Balo, Figen; Karabasevic, Darjan (Mdpi, 2022)
One of the easiest and most common methods for effectively reducing building energy demand is the selection of adequate thermal insulation materials. Thermal insulation is a substantial contribution and an evident, logical and practical first stage toward improving energy performance, particularly in envelope-load-dominant structures located in difficult climate zones. Today's insulating materials come in a broad variety of sizes and shapes, each with its a own qualities. It is well acknowledged that material selection is one of the most difficult and time-consuming aspects of a construction project. Therefore, choosing the right insulation material is also a very important topic to increase energy efficiency. However, it is a complex problem with many criteria and alternatives. This study integrates three different multi criteria decision making methods, which are Fuzzy Best-Worst Method, CRiteria Importance Through Inter-criteria Correlation and Mixed Aggregation by COmprehensive Normalization Technique. In this study, the following eight criteria were taken into account in the evaluation: thermal conductivity, periodic thermal transmittance, specific heat, density, decrement factor, surface mass, thermal transmittance, and thermal wave shift. The first method will be used to find the subjective weights, while the second method will be used to find the objective weights. The third method will be used to rank the insulation materials. According to the results of the Fuzzy Best-Worst Method, the most important criterion was determined as thermal conductivity. According to the results of the CRiteria Importance Through Inter-criteria Correlation, the most important criterion was determined as thermal wave shift. According to the results of the Mixed Aggregation by COmprehensive Normalization Technique, the top 10 insulation materials are as follows: polyisocyanurate, polyurethane (1), polyurethane (2), wood fiber (1), kenaf, jute, cellulose (2), wood fiber (1), XPS (1) and XPS (2). According to the results of the proposed method, polyisocyanurate was determined as the best insulation material for healthier environment. This study makes two contributions to the literature: first, a new hybrid method was developed in this study. Secondly, in this study, the newly introduced Mixed Aggregation by COmprehensive Normalization Technique method was used.
Keywords: building; thermal; insulation materials; MACONT; Fuzzy BWM; CRITIC